Käte Hamburger: Kontext, Theorie und Praxis - Albrecht, Andrea; Löschner, Claudia (De Gruyter eBook-Paket Literatur- und Kulturwissenschaft, Area Studies, 2015)
Käte Hamburger is a major creative force in modern literary studies. Her theoretical work has contributed substantially to advancing the modernization and scientification of philology. Yet the world of literary scholarship has remained relatively unfamiliar with the theoretical and systemic contexts that were the inspiration for Hamburger’s work. The essays in this volume take a major step toward filling this void.